Pelatihan Bahasa Arab Memahami Bacaan Salat, Mewujudkan Ibadah Berkualitas Bagi Warga Perumahan Gubernuran Manggala Makassar - Mahmuddin, Ronny; Syaripudin, Ahmad; Ure, La (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This research aims to teach Arabic about understanding the meaning of prayer readings for residents of the Manggala Makassar Governorate Housing Complex. The problem raised in this research is the extent of the public's understanding regarding prayer reading and the solution, namely the form of implementing an Arabic language training program. This type of research is qualitative research using interview and participant observation methods, starting with observing the conditions of the Manggala Makassar Governorate Housing community using SOAR analysis which then produces work programs and activities. The results of the activities show that the implementation of this research was carried out for two months with an agenda of pre-test, implementation of activities and post-test. Before attending this training, most of the participants did not know the meaning of prayer readings and a small number knew little of the meaning of prayer readings. After attending this training, participants will be able to know the meaning of prayer readings. The post test with a written test instrument from the participants showed very satisfactory grades/scores, namely that they passed the test with a minimum score of 60 to 100. Participants felt there was a significant change in their prayers. The implication of this activity is that it is recommended that activities like this should be continued in other places in general and especially around the Manggala Makassar sub-district and collaborate with religious institutions and government support.